Filter Performance in the Reduction of Hydrogen Sulfide in Biogas - Dalzoto, Lucas Martins; Garcia, Luiz Cláudio; Souza, Eder Carlos Ferreira de; Filho, Renato Zardo; Antunes, Sandra Regina Masetto; Arrúa, Maria Elena Payret; Neto, Pedro Henrique Weirich; Gomes, aime Alberti; Rocha, Nátali Maidl de Souza; Carlos Hugo (International Journal of Advanced Engineering Research and Science, 2019)
The objective of this study was to verify the efficiency of filters in reducing the concentration of hydrogen sulfide (H2S) in biogas. In this case, adsorbent calcined clay and commercial activated charcoalwere employed, both with chemical activation utilizing ferric chloride. The filters were compared with iron filings with the values obtained for standard filters. The experimental design was completely randomized, with six treatments and three replications. The treatments consisted of the collection of H2S present in biogas generated in a biodigester without filtration (control), with an iron filter (ERBR®), with filters formed by calcined clay with and without impregnation by iron, and commercial activated charcoal with and withoutiron impregnation. The adsorbents were characterized in relation to the crystalline or amorphous phases present determined by X-ray diffractometry, the specific surface area, volume and distribution of pore size, and tests of adsorption isotherms in blue methylene. The commercial activated charcoal filter with iron impregnation was the most efficient in the removal of hydrogen sulfide from biogas. Its superior performance with a higher adsorption capacity is due to the large specific surface area of activated charcoal, as well as the chemical interaction between H2S and iron ions impregnated over coal.